The Implementation Of Flashcard in English Teaching Vocabulary at SDS Bina Setia Meradak - Plasia Lexi; Oxtapianus Tawarik; Wanda Giovani (Institut of Shanti Bhuana, 2025)
This study investigated the effectiveness of using flashcards to improve English vocabulary mastery among fifth-grade students at SDS Bina Setia Meradak. The research was motivated by the significant challenge of limited vocabulary acquisition in this rural elementary school, which is characterized by scarce educational resources and non-specialist teachers. The study adopted a pre-experimental design with a one-group pre-test and post-test approach, involving 20 fifth-grade students as participants. Data were collected through a vocabulary test consisting of 20 multiple-choice questions. The results revealed a significant improvement in students' vocabulary mastery. This was evidenced by the substantial increase in the mean post-test score of 81.25 compared to the mean pre-test score of 57.50. A paired-sample t-test showed a statistically significant difference with a p-value of p<0.001, confirming the effectiveness of the intervention. The calculated effect size using Cohen’s d was 3.19333, indicating a very large effect of the flashcard method. This improvement can be attributed to the characteristics of flashcards, which facilitate visualization, repetition, and active student engagement. The study concludes that flashcards are an effective, affordable, and easily prepared instructional medium, particularly suitable for enhancing vocabulary acquisition in resource-limited rural schools. The findings also highlight the need for training non-specialist teachers to adopt innovative teaching methods to improve English language instruction.